2003
DOI: 10.1002/nau.10105
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture reflexotherapy in the treatment of sensory urgency that persists after transurethral resection of the prostate: A preliminary report

Abstract: This study has pointed out that acupuncture reflexotherapy has a real benefit in patients with sensory urgency that persists after transurethral resection of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
32

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 12 publications
1
35
0
32
Order By: Relevance
“…For example, two RCTs ( 8 , 9 ) have shown that the relief of migraine headache lasted 1 year after acupuncture treatment—thousands of times longer than the physiological half life of endorphin ( 47 ) and other common neurotransmitters. Similar long-term benefits of acupuncture have been shown by RCTs on the treatment of shoulder pain ( 48 ), chronic low back pain ( 49 , 50 ), primary dysmenorrhea ( 51 ), spinal cord injuries ( 42 ), urinary urgency ( 41 ) and osteoarthritis ( 5 , 52 , 53 ). This long lasting effect is almost non-existent in conventional therapy using transient mild peripheral nerve stimulation.…”
Section: Modern Biological Models Of Acupuncturesupporting
confidence: 64%
See 1 more Smart Citation
“…For example, two RCTs ( 8 , 9 ) have shown that the relief of migraine headache lasted 1 year after acupuncture treatment—thousands of times longer than the physiological half life of endorphin ( 47 ) and other common neurotransmitters. Similar long-term benefits of acupuncture have been shown by RCTs on the treatment of shoulder pain ( 48 ), chronic low back pain ( 49 , 50 ), primary dysmenorrhea ( 51 ), spinal cord injuries ( 42 ), urinary urgency ( 41 ) and osteoarthritis ( 5 , 52 , 53 ). This long lasting effect is almost non-existent in conventional therapy using transient mild peripheral nerve stimulation.…”
Section: Modern Biological Models Of Acupuncturesupporting
confidence: 64%
“…According to the WHO, 43 auricular points have proven therapeutic value ( 2 ) which consist of more than 10% of the acupuncture points of the entire human body. Numerous RCTs have demonstrated the efficacy of auricular acupuncture ( 38–43 ) while some results are mixed ( 12 ). The non-specific activation of acupuncture points: Therapeutic effect of acupuncture has been achieved by a variety of stimuli ( 1 , 10 ) including needling, injection of non-specific chemicals, electricity, temperature variation, laser and pressure.…”
Section: Modern Biological Models Of Acupuncturementioning
confidence: 99%
“…Acupuncture or electrical stimulation may increase the production of endorphins and analgesic effects to generate a neuromodulation to decrease the high tone of the pelvic floor which is induced by bladder dysfunction [43]. The reflexotherapy of EA can improve sensory urgency in BPH patients with transurethral resection [44]. To sum up, EA increase the voiding volume, Qave, and Qmax of BPH patients with LUTS, possibly through many pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture apply to CV1 (Huiyin), Guanyuan, Sanyinjiao and SP9 (Yinlingquan) 2 weekly sessions for 10 weeks may improve chronic prostatitis/chronic pelvis pain symptoms of adult men [41]. Electrostimulation of Huiyin, CV2 (Qugu), CV4, CV5 (Shimen), BL21 (Weishu), BL23 (Shenshu), BL32 (Ciliao), and auricular points of prostate and external genitalia also can improve LUTS in patients with transurethral resection of the prostate [44]. …”
Section: Discussionmentioning
confidence: 99%
“…The effects of acupuncture on LUTS were well documented in Chinese medicine textbooks and are well-supported by modern research studies [6]. Ricci et al [7] found that electroacupuncture (EA) had better effects in decreasing number of voiding times of urinary urgency that persisted after transurethral resection of the prostate. Kubista et al [8] found that EA could significantly increase the closing pressure in women with stress incontinence as compared with placebo, and Philp et al [9] found that acupuncture increased the bladder capacity in patients with bladder instability.…”
Section: Introductionmentioning
confidence: 97%